Evaluation of Zinc Concentrations in Fruit from Various Pear Strains and Cultivars in China for Establishing a Standard for Zinc-Enriched Pears - Mengjiao Liu; Huili Yu; Longfei Liu; Zhengbo Ma; Jingjie Zhou; Sheng Tang; Lianghuan Wu; Guohai Fu; Yanqing Li; Meng Xu (Horticulturae, 2023)
Zinc (Zn)-enriched pears, which are derived from genetically related cultivars or crops fortified using agronomic methods, have the potential to partly satisfy the human demand for Zn nutrition and diversify consumer choices. However, a standard for the Zn fortification level in pears is lacking, and the disparity in literature-reported fruit Zn concentrations can vary by substantial amounts. Before investigating the Zn concentrations in fruits of the main pear cultivars in China, common sample preparation methods were compared. Among the pre-treatment methods tested, the freeze-dry technique had a greater degree of discrete variation, whereas oven drying (fresh weight) was the optimal method for determining fruit Zn concentrations. Based on the optimal method, no significant distribution patterns of fruit Zn concentration were found among the regions and strains examined. The averaged pulp Zn concentration in all 26 cultivars was 0.72 mg kg−1, with the Hongxiangsu, Jinfeng, and 420 cultivars having the highest concentrations. Combined with the findings from our previous field experiments on Zn-fortified pears, a Zn concentration of ≥0.90 mg kg−1 is the suggested standard for pear enrichment. These results help us to better understand pear Zn nutrition levels and facilitate the marketisation of the fortified fruit.